Finding dorothy ebook A novel. - Letts, Elizabeth (2019)
Discover the story behind The Wonderful Wizard of Oz , the book that inspired the iconic film, through the eyes of author L. Frank Baum’s intrepid wife, Maud, in this richly imagined novel from the #1 New York Times bestselling author of The Eighty-Dollar Champion and The Perfect Horse . “A breathtaking read that will transport you over the rainbow and into the heart of one of America’s most enduring fairy tales.”—Lisa Wingate, author of Before We Were Yours Hollywood, 1938: As soon as she learns that M-G-M is adapting her late husband’s masterpiece for the screen, Maud Gage Baum, now in her seventies, sets about trying to finagle her way onto the set. Nineteen years after Frank’s passing, Maud is the only person who can help the producers stay true to the spirit of the book—she’s the only one left who knows its secrets.   But the moment she hears Judy Garland rehearsing the first notes of “Over the Rainbow,” Maud recognizes the yearning that defined her own life story, from her youth as a suffragist’s daughter to her hardscrabble prairie years with Frank, which inspired The Wonderful Wizard of Oz. Judy reminds Maud of a young girl she cared for in South Dakota, a dreamer who never got a happy ending. Now, with the young girl under pressure from the studio as well as from her ambitious stage mother, Maud resolves to protect Judy—the way she tried so hard to protect the real Dorothy.